Perancangan Sistem Mixing Menggunakan Sensor Load Cell Berbasis Mikrokontroler Arduino Mega 2560 - Hersaputri, Megarini; Ghozi Izzulhaq (EPSILON: Journal of Electrical Engineering and Information Technology, 2023)
In Indonesia, the food and beverage industry grew by approximately 2.54% from 2020 to 2021, with a total revenue of around Rp775.1 trillion according to the Central Statistics Agency (BPS). Specifically, frozen foods such as ice cream, sorbet, and frozen yogurt have gained significant popularity among various consumer groups. The primary stage in the production of frozen foods involves high-quality dough mixing. The designed system consists of an Arduino Mega 2560, load cell sensor, IR obstacle sensor, keypad, single-phase AC motor, and LCD. The load cell sensor is used to measure the weight of ingredients before the mixing process. Test results indicate that the system can weigh ingredients with high accuracy (deviation of 1.82%) and detect obstacles that may cause the motor to not rotate. The system operates in two modes: timer and automatic. In timer mode, the device can set the time according to keypad settings and automatically stop when the time is up. In automatic mode, the mixing machine rotates according to the weight of the ingredients (0.30 kg - 2 kg), with warnings if the ingredients are empty or excessive.